Ảnh hưởng của polyethylene glycol khối lượng phân tử thấp đến các đặc tính cơ nhiệt của polylactide - Quỳnh, Trần Minh (Vietnam Journal of Chemistry, 2014)
Poly(L-lactide), PLLA have been mixed with low molecular weight polyethylene glycol (PEG, 1000 g.mol-1) as a plasticizer in order to prepare plasticized PLLA films with improved flexibility and toughness. The thermal and mechanical properties of the plasticized PLLA were significantly changed by plasticization effect of PEG. The glass transition temperature (Tg), melting temperature (Tm) of the plasticized PLLA were much reduced while their degree of crystallization increased with the increasing of PEG amount in the materials. Thermal stability of the plasticized PLLA samples was also reduced by adding of the plasticizer due to thermal decomposition of PEG even at low temperature. Flexibility of the plasticized PLLA was much improved, whereas its tensile strength and modulus slightly reduced. The elongation at break of PLLA/10%PEG was about 80 %, much higher than 4.6 % in comparison with the initial PLLA. The results suggested that PEG was miscible with PLLA into the plasticized material with high flexibility and toughness, met the requirements in industrial applications. Keywords: Poly(L-lactide), polyethylene glycol, plasticization effect, thermal stability, toughness.